2017
DOI: 10.12659/msm.898449
|View full text |Cite
|
Sign up to set email alerts
|

miR-340 Inhibits Proliferation and Induces Apoptosis in Gastric Cancer Cell Line SGC-7901, Possibly via the AKT Pathway

Abstract: BackgroundGastric cancer is among the most common types of cancer, with high morbidity and mortality. MicroRNAs (miRNAs) play vital roles in the tumorigenesis and biology of gastric cancer. This study aimed to reveal the role of miR-340 in gastric cancer cell proliferation and apoptosis and to elucidate the potential mechanisms.Material/MethodsHuman gastric cancer cells SGC-7901 were used in this study for cell transfection with miR-340 mimic or inhibitor. After transfection, cell viability, proliferation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…Finding specific miRNAs and its target genes that participate in the occurrence of tumors is important for the diagnosis and treatment of malignant tumors. We found that miR‐340 is an impaired regulatory factor in many cancers, such as breast cancer and gastric cancer (Yu et al, ; Shi et al, ). Therefore, miR‐340 is the target of this study to investigate whether miR‐340 is abnormally expressed in cervical cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Finding specific miRNAs and its target genes that participate in the occurrence of tumors is important for the diagnosis and treatment of malignant tumors. We found that miR‐340 is an impaired regulatory factor in many cancers, such as breast cancer and gastric cancer (Yu et al, ; Shi et al, ). Therefore, miR‐340 is the target of this study to investigate whether miR‐340 is abnormally expressed in cervical cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In CRC, miR-340 was observed to target RLIP76 50 and REV3L 64 to mediate cell apoptosis. Moreover, miR-340 increased the levels of apoptosis-related factors pro-caspase 3, cleaved-caspase 3, and Bax, but inhibited Bcl-2 in SGC-7901 cells 18 . A similar phenomenon was also observed in the endometrial carcinoma cell line RL 95-2 65 .…”
Section: Functional Roles Of Mir-340 In Cancersmentioning
confidence: 92%
“…Recently, a number of studies have reported that miR-340 plays a critical role in tumor initiation and progression, by targeting multiple oncogenes such as SKP2 , FHL2 , c-Met , and ROCK1 ( Table 1 ). Some signaling pathways related to tumorigenesis, such as AKT 18 , SOCS3/JAK-STAT 19 , and Wnt/β-catenin pathways 20 , were shown to be suppressed by miR-340.…”
Section: Introductionmentioning
confidence: 99%
“…). miR‐340 is a tumor suppressor in melanoma and other cancers . We previously highlighted a pathway‐specific model of miRNA‐directed regulation in melanoma via miR‐340‐dependent modulation of the MAPK pathway, the most commonly dysregulated pathway in melanomas .…”
Section: Introductionmentioning
confidence: 99%
“…We previously highlighted a pathway‐specific model of miRNA‐directed regulation in melanoma via miR‐340‐dependent modulation of the MAPK pathway, the most commonly dysregulated pathway in melanomas . miR‐340 regulates proliferation, migration, and invasion in melanoma cells as well as in breast, lung, osteosarcoma, glioma, and other cancers . However, miRNA effects are pleiotropic, and although some miR‐340 targets have been identified, the entire targetome is unknown.…”
Section: Introductionmentioning
confidence: 99%